2012
DOI: 10.1089/end.2011.0407
|View full text |Cite
|
Sign up to set email alerts
|

The Penetration of Renal Mass Biopsy in Daily Practice: A Survey Among Urologists

Abstract: RMB is not yet applied widely in urologic practice, with academic urologists performing RMB less infrequently. Core biopsies are still preferred, although combined with cytologic punctures by a considerable number of responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 21 publications
(19 reference statements)
0
28
0
1
Order By: Relevance
“…The development of a non-invasive “liquid biopsy” represents a significant innovation in the field of precision medicine. It is capable of replacing, or at least augmenting the use of invasive biopsy which has limited success and associated complications [3, 4]. Liquid biopsies, owing to their minimally invasive nature, are associated with significantly less morbidity and can be scheduled more frequently to provide a personalized snapshot of disease at successive time points.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a non-invasive “liquid biopsy” represents a significant innovation in the field of precision medicine. It is capable of replacing, or at least augmenting the use of invasive biopsy which has limited success and associated complications [3, 4]. Liquid biopsies, owing to their minimally invasive nature, are associated with significantly less morbidity and can be scheduled more frequently to provide a personalized snapshot of disease at successive time points.…”
Section: Introductionmentioning
confidence: 99%
“…These results were similar to the results in our survey where 67% of responding institutions performed core biopsies, 5% performed FNA, and 28% performed both core biopsy and FNA. 15 Ninety-five percent of the institutions in our study and 92% of respondents in the study by Barwari et al who performed a biopsy of the tumor used core biopsy or a combination of core biopsy with FNA. In our survey we also asked when the biopsy was performed (prior to the day of the procedure or on the day of the procedure prior to ablation) to determine whether knowledge of the biopsy result was known prior to thermal ablation.…”
Section: Discussionmentioning
confidence: 64%
“…4 Barwari et al sent a questionnaire to members of the Endourological Society to assess the use of renal mass biopsy in current urologic practice. 15 Despite a low response rate (10.2%, 190 responders), they found that 73% of responders ''never'' or ''rarely'' performed a renal mass biopsy. Tan et al evaluated patient and tumor characteristics associated with percutaneous renal mass biopsy among patients with small renal masses at a single institution.…”
Section: Discussionmentioning
confidence: 95%
“…A survey among urologists has shown that the use of RMB in characterisation of the renal mass remains limited at present, with only a minority of clinicians using biopsy in their practice . Cost‐effectiveness models have been developed to further evaluate the potential impact of RMB.…”
Section: Resultsmentioning
confidence: 99%